Interventions to promote cost-effectiveness in adult intensive care units: consensus statement and considerations for best practice from a multidisciplinary and multinational eDelphi study - Kansal, A.; Latour, Jos; See, K.C.; Rai, S.; Cecconi, M.; Britto, C.; Conway Morris, A.; Dominic Savio, R.; Nadkarni, V.M.; Rao, B.K.; Mishra, R. (2023)
Background: There is limited evidence to guide interventions that promote cost-effectiveness in adult intensive care units (ICU). The aim of this consensus statement is to identify globally applicable interventions for best ICU practice and provide guidance for judicious use of resources. Methods: A three-round modified online Delphi process, using a web-based platform, sought consensus from 61 multidisciplinary ICU experts (physicians, nurses, allied health, administrators) from 21 countries. Round 1 was qualitative to ascertain opinions on cost-effectiveness criteria based on four key domains of high-value healthcare (foundational elements; infrastructure fundamentals; care delivery priorities; reliability and feedback). Round 2 was qualitative and quantitative, while round 3 was quantitative to reiterate and establish criteria. Both rounds 2 and 3 utilized a five-point Likert scale for voting. Consensus was considered when > 70% of the experts voted for a proposed intervention. Thereafter, the steering committee endorsed interventions that were identified as ‘critical’ by more than 50% of steering committee members. These interventions and experts’ comments were summarized as final considerations for best practice. Results: At the conclusion of round 3, consensus was obtained on 50 best practice considerations for cost-effectiveness in adult ICU. Finally, the steering committee endorsed 9 ‘critical’ best practice considerations. This included adoption of a multidisciplinary ICU model of care, focus on staff training and competency assessment, ongoing quality audits, thus ensuring high quality of critical care services whether within or outside the four walls of ICUs, implementation of a dynamic staff roster, multidisciplinary approach to implementing end-of-life care, early mobilization and promoting international consensus efforts on the Green ICU concept. Conclusions: This Delphi study with international experts resulted in 9 consensus statements and best practice considerations promoting cost-effectiveness in adult ICUs. Stakeholders (government bodies, professional societies) must lead the efforts to identify locally applicable specifics while working within these best practice considerations with the available resources.